Bez retushi . Bez retushi . Without Retouching . Без ретуши - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Human right activist Elena Bonner answers the questions of the journalists of different periodicals. Featured in the program: Bonner, Elena Georgievna (Human Rights Activist) Contributors: Torchinskii, Sergei (Anchor); Krasnova, Tat'iana (Anchor) Правозащитница Елена Боннэр отвечает на вопросы журналистов различных изданий. В программе участвуют: Боннэр, Елена Георгиевна (Правозащитница) Создатели: Торчинский, Сергей (Ведущий/Ведущая); Краснова, Татьяна (Ведущий/Ведущая)